Mechanism that governs the electro-optic response of second-order nonlinear polymers on silicon substrates - Schulz, K. Marvin; Prorok, Stefan; Jalas, Dirk; Marder, Seth R.; Luo, Jingdong; Jen, Alex K-Y.; Zierold, Robert; Nielsch, Kornelius; Eich, Manfred (Optical Materials Express, 2015)
We use a modified Teng-Man technique to investigate the poling induced electro-optic activity of chromophore-doped organic polymers poled on silicon substrate in a thin film sample configuration. We reveal a fundamental difference between the poling processes on silicon substrate and ITO substrate. The electro-optic activity for polymers poled on silicon substrate is reduced which we ascribe to space charge formation at the silicon - organic interface that distorts the field distribution in the polymer film during high field poling, and therefore limits the effective induced polar order. We demonstrate that the electro-optic activity on silicon substrate can be improved by inserting a 5 nm thin dielectric layer of Al2O3q between the silicon substrate and the polymer which reduces the leakthrough current during poling, thereby allowing for higher applicable poling voltages.
CRIS-Team Scopus Importer:2023-03-20